Pediatric cochlear implantation: Experience in Thai patients - Chanida Kanchanalarp (2018)
Objective: This study was to evaluate the result of cochlear implantation in Thai pediatric patients from 1999-2003. Design: A prospective, open-labeled study. Setting: University teaching hospital. Material and Method: Long term surgical and audiologic results comparison after cochlear implantation in 2 cases with Mondini anomality, 7 normal cochlea cases and a case of post meningitis post lingual child. Main out come measures: Speech perception tests battery. Results: Among 10 children, 8 were implanted with Nucleus 22/24; the other two were implanted with Med-el device system. The pre-operated cochlea in 2 cases showed Mondini deformity; both had gushers during the operation with a good outcome. The other 8 cases had normal cochlea although one was deaf from bacterial meningitis. There were 3 re-implantations. Speech production and perception was improved faster in the two children implanted with Med-el than those implanted with Nucleus devices. Conclusion: Cochlear implantation in Mondini cases can be successful in speech production and perception. Speech perception ability depended on the age of implantation and preoperative rehabilitation.